2021
DOI: 10.1371/journal.pone.0256177
|View full text |Cite
|
Sign up to set email alerts
|

Low-field and variable-field NMR relaxation studies of H2O and D2O molecular dynamics in articular cartilage

Abstract: Osteoarthritis (OA) as the main degenerative disease of articular cartilage in joints is accompanied by structural and compositional changes in the tissue. Degeneration is a consequence of a reduction of the amount of macromolecules, the so-called proteoglycans, and of a corresponding increase in water content, both leading to structural weakening of cartilage. NMR investigations of cartilage generally address only the relaxation properties of water. In this study, two-dimensional (T1-T2) measurements of bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…In general, small and highly polar molecules meet the requirements for strong adsorption, and relaxation governed by RMTD has first been shown for water and D 2 O; the agreement of the T 1 (ω) dispersion of both 1 H and 2 H nuclei in these molecules can be seen as proof of the dominating intramolecular nature of the relaxation process . Alkanes in porous glass or aluminum oxide, on the other hand, come close to the weak interaction limiting case and have shown very low T 1 (ω) dispersion. , It is quite remarkable that in the opposite case of an inorganic surface covered with organic cokeactually, the by-product of a naphtha refining process inside a catalyst and therefore not unlike the bitumen layer deposited on the rock surface in this studythe affinity of alkanes to this coke layer generated very similar T 1 (ω) dispersion as soon as a fraction of the native Al 2 O 3 surface was covered with the organic substance but a flat dispersion with the native surface . In that study, the dispersion of water 1 H nuclei was found to maintain a very pronounced relaxation dispersion irrespective of the coke content, but the surface fractal dimension obtained from the RMTD model changed in full agreement with the surface roughness obtained by independent methods.…”
Section: Theoretical Modelsmentioning
confidence: 94%
“…In general, small and highly polar molecules meet the requirements for strong adsorption, and relaxation governed by RMTD has first been shown for water and D 2 O; the agreement of the T 1 (ω) dispersion of both 1 H and 2 H nuclei in these molecules can be seen as proof of the dominating intramolecular nature of the relaxation process . Alkanes in porous glass or aluminum oxide, on the other hand, come close to the weak interaction limiting case and have shown very low T 1 (ω) dispersion. , It is quite remarkable that in the opposite case of an inorganic surface covered with organic cokeactually, the by-product of a naphtha refining process inside a catalyst and therefore not unlike the bitumen layer deposited on the rock surface in this studythe affinity of alkanes to this coke layer generated very similar T 1 (ω) dispersion as soon as a fraction of the native Al 2 O 3 surface was covered with the organic substance but a flat dispersion with the native surface . In that study, the dispersion of water 1 H nuclei was found to maintain a very pronounced relaxation dispersion irrespective of the coke content, but the surface fractal dimension obtained from the RMTD model changed in full agreement with the surface roughness obtained by independent methods.…”
Section: Theoretical Modelsmentioning
confidence: 94%
“…Conventional T2* mapping has been suggested as an alternative measure of ligament integrity because it may better capture the highly organized collagen structure and low water content (19). By accounting for B 0 inhomogeneity due to paramagnetic and diamagnetic effects, T2* is theorized to reflect the degree of collagen fibre orientation and alignment as well as the spin-to-spin interactions of protons bound to collagen (20,21). Consequently, T2* is widely considered a surrogate marker of ligament integrity and water content, collagen matrix organization, fibre orientation, and fibre alignment (19,20,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%